Capital Structure, Return on Equity, Earnings Per Share on Firm Value Through Stock Return - Andi Jenni Indriakati; Masyadi (Jurnal Manajemen, 2026)
This study aims to analyze the influence of Debt to Equity Ratio, Return on Equity, and Earnings per Share on company value, and to evaluate the role of Stock Return as a moderating variable for companies in the health sub-sector on the Indonesia Stock Exchange. This study uses a quantitative approach with a sample of 13 companies selected through purposive sampling. Data were obtained from annual financial statements and analyzed using panel data regression and hypothesis testing. The results indicate that, in part, DER does not significantly influence firm value, whereas ROE and EPS have positive and significant effects. Stock Return does not moderate the relationship between DER and firm value, but it successfully strengthens the influence of ROE and EPS on firm value. Investors should pay attention to profitability indicators when making investment decisions and encourage companies to improve their financial performance to strengthen market value.